Economic Value Added: A Conceptual Framework - Singh, Tarika; Mehta, Seema (Gyan Management Journal, 2011)
The usefulness of traditional accountin!_J measure, such as earnings per share (EPSJ, return on assets _ROA) and return on equity (ROE), and their effect on shareholder (market) value, has been discussed :or some time. Since the 1990s, strong arguments have been raised in favour of economic value added
Keywords: Shareholder Value; Value based measures; EVA